Rischio stress tra il personale degli asili nido/scuole dell’infanzia della Municipalità di Venezia e Marghera / Work-related stress in nursery school educators in the Venice and Marghera districts - Camerino, D.; Fichera, G.P.; Punzi et al., S. (La Medicina del Lavoro, 2011)
«Work-related stress in nursery school educators in the Venice and Marghera districts». Background: Based on an investigation on organizational well-being in the Municipality of Venice (2009), we examined 110 public nursery school and preschool teachers working in the Venice and Marghera districts. Objectives: The aim of this study was to develop and implement a procedure for work-related stress assessment and management in Municipality of Venice, in the light of Law 81/2008. Methods: Occupational stress and its impact on teachers’ well-being and health were assessed by means of self-administered questionnaires and semi-structured interviews. Descriptive analyses were conducted to compare teachers’ data with those concerning employees operating in other services in the Venice and Marghera districts. Results: According to the results, while nursery school and preschool teachers work with considerable commitment, vigor, dedication and involvement, problems were observed related to: assignment of administrative tasks without appropriate support from the district offices; difficult access to support services; shortage of temporary teachers and auxiliary personnel and, limited to some facilities, lack of adequate physical space devoted to teaching activities. Such adverse conditions result in an increase in vigilance levels required to ensure children’s safety. Personnel also suffer from a lack of career prospects, with scarce opportunities for contact with other facilities in the area and inadequate involvement in the decisional processes at Municipality level. Conclusions: Improving such adverse conditions could solve the current marginalization of public nursery school and preschool teachers and encourage mutual exchange of information, which would in turn favour more appropriate methods of managing each single facility.